1992
DOI: 10.1039/ft9928801425
|View full text |Cite
|
Sign up to set email alerts
|

Triple-ion formation and acid–base strength of ions in protophobic aprotic solvents

Abstract: The formation of symmetrical triple ions [2M+ + X -e M,X+, (K,); M + + 2X-e MX; , ( K 3 ) ; K, = K3] and the quadrupole [M2X+ + X-s M2X, , ( K 4 ) ; M+ + MX; e M, X, , ( K 5 ) ; K, = K 5 ] , in addition to ion-pair formation [M+ + X-s MX, (K,)] from various uni-univalent salts were examined by means of conductometry in acetonitrile, benzonitrile and propylene carbonate. The salts are made from bases (B) and acids (HX) of varying strength.For diethylcyclohexylammonium chloride C(O.4-6.0) x

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Additional limitations lay in the formation of triple ionic or higher ionic aggregates (see, e.g. [65,66]). …”
Section: Acetonitrile As Solventmentioning
confidence: 99%
“…Additional limitations lay in the formation of triple ionic or higher ionic aggregates (see, e.g. [65,66]). …”
Section: Acetonitrile As Solventmentioning
confidence: 99%
“…So the ion-pairs attract the free +ve and Àve ions present in the solution medium as the distance of the closest approach of the ions becomes a minimum; as a result, the possibility of higher aggregation through hydrogen bonding increases in low permittivity media. 17,18 This results in the formation of triple-ions, which acquire the charge of the respective ions in the solution 19 i.e.,…”
Section: Triple-ion Formationmentioning
confidence: 99%
“…Theories of conductivity for higher ionic strengths have been highly However, the limited information provided by transport phenomena may lead to incorrect structures for solutions unless the species present in the solutions are fully comprehended. By using computer simulations, we have demonstrated that Shedlovsky analyses of conductivity data with extremely strong associations between or among ions (the formation of ion pairs and strong triple ions from uni-univalent salts) can give even a "pseudo" association constant of zero (Ka = O).4, 5 Sixty years ago, Fuoss and Kraus supposed that triple ion formation from a uni-univalent electrolyte by the action of electrostatic forces could occur only in very low dielectric constant media.6-8 It must be a very difficult task to elucidate the "proper" iilteractions (ion-solvent, ion-ion, and solventsolvent) in low-permittivity media, because of the strong Coulombic attraction between ions. Fuoss proposed a new conductance e q~a t i o n ;~ however, he commented that it may not be applied to data for solvents of dielectric constant lower than about 10 because interionic Coulombic forces become strong enough to produce overlap of three or more cospheres (in his model).…”
Section: Introductionmentioning
confidence: 99%